Whether or Not Indonesia-Based Companies Consider Anti-Corruption Acts Important as Its Countrymen do - Paulina Permatasari; Felix Wijaya Indra Putra; Vania Natasha (Indonesian Management and Accounting Research, 2017)
In Indonesia, the act of corruption is a prevalence. Anti-corruption acts have been waged for years, yet the problem of corruption remains unresolved. The rising awareness on sustainability accounting urges many companies to support anti-corruption acts. Whether or not these companies support is a different issue. Although GRI Standards view anti-corruption acts as an economic aspect, the corruption is an act of defiling the society’s trust and constitutes as a highly sensitive issue in a democratic country such as Indonesia. This study applies sensemaking theory to determine that Indonesia-based companies should have supported the anti-corruption acts and disclose them in their sustainability reports. A thorough content analysis on the sustainability reports of 80 Indonesia-based companies has been conducted with a view to finding disclosures of anti-corruption acts. The result shows that most of these companies do not disclose their anti-corruption acts. In a sensible sense, the commitments to supporting anti-corruption acts by companies result in the disclosure of such anti-corruption acts. The finding evidences how Indonesian company are still lacking in acts against corruption.